Automated calibration system for a digital thermo-hygrometer using image processing approaches and wireless communication - Tongbai, Jettana (Bulletin of Applied Sciences, 2024)
This research presents an automated calibration system for the calibration of a Digital Thermo-Hygrometer not equipped with a communication interface using digital image processing technology and a real-time wireless communication method to reduce time-consuming calibrations and reduce human errors. This research proposes a solution based on an ESP32-CAM, a small and low-cost camera module, capturing a meter image and transferring it to a web server processing using the seven-segment optical character recognition (SSOCR) method. The measurement and calibration results are presented in a dashboard accessible through the web browser. The experimental results validate the effectiveness of both algorithm and user applications, offering overall performance comparable with manual calibrating processes. In particular, the experimental results on the built-up system show that the proposed image recognition methods provide an average accuracy of 96.48%.